KOMUNIKASI DAKWAH PEMERINTAH DALAM MEMBANGUN DESA RELIGIUS DI JEPARA - Miftahul Huda (Mediakita, 2020)
The village of Margomulyo Jepara has wide and varied da'wah challenges in line with the dynamics of globalization and the development of information technology whose negative effects cause various konds of socio religiuos problems. Under these conditions, the village government carried out da'wah communication in order to overcome these problems and build a religious village. This research is a qualitative research methods as well as policy research. Data collection techniques in this study were through interviews, observation, and documentation. The data analysis techniques used inductive and descriptive narrative forms. The result of this research is that the da'wah communication carry out the Margoyoso village government is carried out through several stages such as problem formulation, policy formulation, legitimacy, communication and socialization. The background for the birth of this policy was due to the socio-religious problems and poltical agenda of the village government. The da'wah messages in this study consist of morning prayers in congregation, turning off the television after maghrib, let's recite the recitation and compulsory Early Madrasah which is formulated based on the results of deliberations with the village government, religious leader, community leaders, and religious social organizations. The communication process is carried out with two approaches, namely cultural and structural approaches.